Estudo experimental de um difusor cônico aplicado a um microgerador eólico - TANOUE, Atamy Reis (2018)
The conical diffuser installed around the turbine causes an increase in the speed of the wind that is incident on its rotor, causing an increase of efficiency in the generation of electric energy. Once the wind behavior inside the diffuser is known, it is possible to determine the ideal region for the turbine installation (higher speeds) in order to take advantage of the higher available kinetic energy. This global increase in wind speed reaching the turbine rotor causes an increase in energy extraction. The present work has the objective of evaluating the increase of the electric power generation of a wind turbine with the installation of conical diffusers, besides an experimental survey about the behavior of the air flow in a conical diffuser. In this way, in addition to evaluating the influence of the diffuser geometry on the generation of electric energy, the present work seeks to gather information that complements the mathematical model proposed by Barbosa (2013), which provides for the distribution of speeds within the diffuser in function of its geometry. The results obtained by this work indicated that in fact there is the increase of tension due to the presence of the diffuser around the turbine, the increase of velocity was of the order of 21%, while the increase of velocity electric tension was of the order of 16 %. It also showed that the behavior obtained is compatible with the available literature and the results of work on the subject.